United States : Financial Sector Assessment Program-Technical Note-Securities-Fund Management; Equity and Derivatives Trading; and Virtual Assets and Virtual Asset Service Providers. (IMF Staff Country Reports; Country Report ;, 2020)
This technical note considers the regulation and supervision of fund management and equity and derivatives trading in the United States (U.S.). As one of the main destinations for household savings and a key provider of funding to U.S. corporates, investment funds play a major role in the U.S. financial system. Distortions to equity trading could cause significant loss of confidence in markets, while international post-crisis reforms for OTC derivatives have underlined the importance of greater transparency and the value of central clearing. U.S. companies have also traditionally raised more finance through equity and other capital markets than through bank lending, and so capital markets are of greater structural significance in the U.S. than in some other jurisdictions.